Ambulatory colonoscopy under sedoanalgesia in adult patients with and without irritable bowel syndrome: A prospective, cross-sectional, and double-blind comparison - Tuncalı, Bahattin; Araz, Coşkun; Çelebi, Arzu (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: It is unclear whether patients with irritable bowel syndrome (IBS) require a high dose of sedatives during colonoscopy. In this study, we investigated the pre-procedural anxiety levels, sedative consumption, procedure times, complications, and patient’s satisfaction between patients with IBS and controls for ambulatory colonoscopy under sedation. Materials and Methods: Rome III criteria were used in the diagnosis of IBS. Anxiety levels were measured using Spielberger’s State-Trait Anxiety Inventory (STAI) and Beck Anxiety Inventory (BAI). Patients received a fixed dose of midazolam (0.02 mg/kg), fentanyl (1 μg/kg), ketamine (0.3 mg/kg), and incremental doses of propofol under sedation protocol. Demographic data, heart rate, blood pressure, and oxygen saturation were measured. Procedure times, recovery and discharge times, drug doses used, complications associated with the sedation, and patient’s satisfaction scores were also recorded. Results: The mean Trait (p=0.015), State (p=0.029), Beck anxiety scores (p=0.018), the incidence of disruptive movements (p=0.044), and the amount of propofol (p=0. 024) used were significantly higher in patients with IBS. There was a decline in mean systolic blood pressure at the 6th minute in patients with IBS (p=0.026). No association was found between the sedative requirement and the anxiety scores. Conclusion: Patients with IBS who underwent elective colonoscopy procedures expressed higher pre-procedural anxiety scores, required more propofol consumption, and experienced more disruptive movements compared with controls. On the contrary, the increased propofol consumption was not associated with the increased pre-procedural anxiety scores. Cite this article as: Tuncalı B, Araz C, Çelebi A. Ambulatory colonoscopy under sedoanalgesia in adult patients with and without irritable bowel syndrome: A prospective, cross-sectional, and double-blind comparison. Turk J Gastroenterol 2018; 29: 335-41.